Differences in the Spiritual Welfare Levels of the Elderly Who Have Spouses and Without Spouses - Melvanriz Fahlevi; Reni Zulfitri; Riri Novayelinda (CV. Rayyan Dwi Bharata, 2023)
Introduction: Most of the elderly who have spouses have a high level of spiritual well-being, but some also have moderate and low levels of spiritual well-being. This is also experienced by the elderly who do not have a life partner, some have moderate and low levels of spiritual well-being, but some also have high levels of high spiritual well-being. Purpose: this study aims to determine the difference in the spiritual well-being of the elderly who have a spouse and without a spouse. Place of Research: Rejosari Health Center Working Area. Methods: This study used a quantitative design using a comparative study method. The approach used was cross sectional. Results: There is no difference in the level of spiritual well-being of the elderly who have a spouse and without a spouse (Sig. (2-tailed) = 0.228, 0.05). Conclusion: There is no difference in the level of spiritual well-being of the elderly who have spouses and those without spouses. Suggestion: Future researchers can examine the factors that affect the spiritual well-being of the elderly with or without a spouse.